There exists only one tumor necrosis factor - S. A. Nedospasov (Медицинская иммунология)
Tumor necrosis factor (TNF) is an important proinflammatory and immunoregulatory cytokine with several unique protective and homeostatic functions. Since TNF is a mediator of several pathologies and is a part of “cytokine storm”, its significance for clinical immunology is due to the fact that this cytokine is a target of commonly used anti-cytokine therapy in autoimmune and inflammatory diseases. In scientific literature and textbooks TNF is often goes as “TNFa”, implying the existence of at least TNFβ (indeed, such term was used for about 10 years in 80s and 90s to designate lymphotoxin). However, already 25 years ago such designation of lymphotoxin was cancelled “on scientific grounds”. Therefore, both in Russian and in English the term TNF should be used without “alpha”. Labels of the reagents related to TNFb that are offered by commercial companies are misleading.